The great Ordovician biodiversification event - Webby, B. D. (Critical moments in paleobiology and earth history series., 2004)
Two of the greatest evolutionary events in the history of life on Earth occurred during Early Paleozoic time. The first was the Cambrian explosion of skeletonized marine animals about 540 million years ago. The second was the ""Great Ordovician Biodiversification Event, "" which is the focus of this book. During the 46-million-year Ordovician Period (489--443 m.y.), a bewildering array of adaptive radiations of ""Paleozoic- and Modern-type"" biotas appeared in marine habitats, the first animals (arthropods) walked on land, and the first non-vascular bryophyte-like plants (based on their